Best Buys and Own Brands: Investment Platforms' Recommendations of Mutual Funds. (20th May 2020) - Cookson, Gordon; Jenkinson, Tim; Jones, Howard; Martinez, Jose Vicente
Abstract: Individuals increasingly buy mutual funds via online platforms, whose "best-buy" recommendations heavily influence flows. As intermediaries of mutual funds, platforms provide none of the unobservable interaction or intangible benefits of brokers, and so allow clean tests of the determinants, influence, and value of their fund recommendations. Using unique U.K. data, we find that platforms favor "own-brand" funds and those paying them a higher commission share. Investors discount own-brand recommendations, but not those paying high commission shares (which were not observable in the United Kingdom). A regulatory ban on commission sharing lowered costs and improved the informativeness of platform recommendations.